Pembelajaran Kreatif Untuk Menanamkan Nilai Agama Dan Moral Anak Usia Dini Usia 5 - 6 Tahun di Taman Kanak-Kanak Mardhotillah Kelurahan Gunung Kembang Kecamatan Sarolangun Kabupaten Sarolangun Jambi - Rita Lasmi; Badarus Syamsi; Siti Raudatul Jannah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to describe the planning, implementation and evaluation of instilling religious and moral values ​​in Mardhotilah Kindergarten, Gunung Kembang Village, Sarolangun District Jambi. This research uses a qualitative approach with a descriptive type of research conducted in kindergarten with the research subjects being the school principal, teachers and children. Data collection was carried out using interview, observation and documentation techniques. Data were analyzed using qualitative descriptive analysis techniques. Data validity is carried out by triangulating sources and techniques. The research results show; 1) Planning is made by the teacher as a religious team which is arranged into a Semester (Prosem), Weekly Program Plan (RPPM) specifically for instilling religious and moral values, which is divided into seven aspects, namely, aqidah, akhlaq, worship, memorizing letters, memorizing prayers/hadith, Al-Qur'an signals, and mahfudhot; and RPPH. 2) In its implementation, instilling religious and moral values ​​uses various methods, including the habituation method, the example method, the field trip method, the storytelling method and the play method which are applied in various activities carried out by children from the time the child arrives at school until the child returns home from school; 3) Evaluation is carried out through observation assessments, anecdotal notes and portfolios for semester report cards as well as follow-up programs in the form of enrichment; 4) If there are non-Muslim students, the school gives students the option to choose other universal subjects.